Evaluation of School Literation Movement Programs in Jakarta Selatan Wilayah II High School, Kecamatan Tebet - Sakinah, Sakinah; Karnati, Neti; Supadi, Supadi (International Journal for Educational and Vocational Studies, 2020)
This study aims to determine the implementation of the School Literacy Movement or Gerakan Literasi Sekolah (GLS) program carried out in the South Jakarta State High School area II in Tebet sub-district. This research is a type of evaluation research with a qualitative approach using the gap evaluation model or Discrepancy Evaluation Model (DEM) developed by Malcom Provus. So that the implementation of the GLS program in terms of design, installation, process, and product. The data is obtained through observation, interviews, and study documents. Principals and teachers in these schools have implemented a school literacy movement program by the indicators of the school literacy movement contained in the master design of the school literacy movement in secondary schools. The condition of the school has fulfilled the adequacy and adequacy of facilities and infrastructure that support the school literacy movement program. The competencies of school principals and teachers have been able to develop the school literacy movement program The results of the study stated that the level of achievement of the GLS program in Tebet sub-district high schools was in the High category. This means that for the most part, even all program indicators have been implemented or are available according to criteria.